The functional organization of mitochondrial genomes in human cells. - Iborra, F; Kimura, H; Cook, P (2004)
BACKGROUND: We analyzed the organization and function of mitochondrial DNA in a stable human cell line (ECV304, which is also known as T-24) containing mitochondria tagged with the yellow fluorescent protein. RESULTS: Mitochondrial DNA is organized in approximately 475 discrete foci containing 6-10 genomes. These foci (nucleoids) are tethered directly or indirectly through mitochondrial membranes to kinesin, marked by KIF5B, and microtubules in the surrounding cytoplasm. In living cells, foci have an apparent diffusion constant of 1.1 x 10(-3) microm2/s, and mitochondria always split next to a focus to distribute all DNA to one daughter. The kinetics of replication and transcription (monitored by immunolabelling after incorporating bromodeoxyuridine or bromouridine) reveal that each genome replicates independently of others in a focus, and that newly-made RNA remains in a focus (residence half-time approximately 43 min) long after it has been made. This mitochondrial RNA colocalizes with components of the cytoplasmic machinery that makes and imports nuclear-encoded proteins - that is, a ribosomal protein (S6), a nascent peptide associated protein (NAC), and the translocase in the outer membrane (Tom22). CONCLUSIONS: The results suggest that clusters of mitochondrial genomes organize the translation machineries on both sides of the mitochondrial membranes. Then, proteins encoded by the nuclear genome and destined for the mitochondria will be made close to mitochondrial-encoded proteins so that they can be assembled efficiently into mitochondrial complexes.